2019
DOI: 10.1016/j.arabjc.2014.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Mn3O4 nanobelts through the solvothermal process and their photocatalytic property

Abstract: Hausmannite Mn 3 O 4 nanobelts were synthesized from manganese acetate and potassium hydroxide precursors in the presence of melamine-ethanol-distill water via the reflux and solvothermal methods. X-ray diffraction (XRD) and Fourier transform infrared (FT-IR) spectroscopes confirm the composition of the as-prepared product. Field emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), selected area electron diffraction (SA-ED), high resolution transmission electron microscopy (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 55 publications
(45 reference statements)
0
20
0
Order By: Relevance
“…24-0734. The characteristic diffractogram of formed sheet like Mn 3 O 4 nano crystals and nano particle synthesized by solvothermal approach without melamine are corroborated [34].…”
Section: Solvothermal Methodsmentioning
confidence: 55%
See 3 more Smart Citations
“…24-0734. The characteristic diffractogram of formed sheet like Mn 3 O 4 nano crystals and nano particle synthesized by solvothermal approach without melamine are corroborated [34].…”
Section: Solvothermal Methodsmentioning
confidence: 55%
“…It functions as capping ligand. It also controls the discharge speed of Mn 2þ ions and panels the growth direction of Mn 3 O 4 nano belts [34]. It is well evidenced that the establishment of single crystalline 1D-nanobelts is through well-aligned lattice lines.…”
Section: Solvothermal Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…The combination of several different characterization techniques revealed that addition of manganese ions resulted in Mn 3 O 4 grafted on the surface of the ZnO nanoparticles. Mn 3 O 4 has photocatalytic properties [55,56] but only at a pH below 4 [57]. In the present study, Rhodamine-B, an acidic dye, was used as a model organic pollutant to examine the photocatalytic activity of manganese-added ZnO.…”
Section: Cause Of Conflicting Results In the Past Studiesmentioning
confidence: 99%